Mapping the density of particles over the surface of asteroid (101955) Bennu - Winter, Othon C. [UNESP]; Amarante, André [UNESP] (My University, 2017)
In the present work we study the motion of particles near the surface of Bennu. An application of the results is to give assistance for the selection of the sample site. Considering the gravitational potential given by the polyhedral model of Bennu (1348 vertices, 2692 faces), we numerically simulated many samples of several thousand test particles initially located randomly in a cloud around the asteroid. We have investigated eccentric and inclined orbits, and we also adopted different particle sizes, from dust grains up to small particles. It is already known that Bennu has eight equilibrium points around it, and according to the adopted density, a couple of them might be stable. The influence of the equilibrium points is very strong on the orbital evolution of the particles. In the long term dynamics most of the particles collided with the asteroid surface. From our results were generated map diagrams indicating the amount of collided particles distributed over the surface of Bennu. They show the spots of very high collision rates, where are expected to be fully covered of particles, and also those where it is expected to be cleaner (sites of very low collision rates). These diagrams are made for a range of different particle sizes and also, with and without taking into account the solar radiation pressure in the dynamics of the orbital evolution. In order to make the selection for the sample site, we believe that these results might be extremely useful for the OSIRIS-REX mission.
Keywords: Asteroid (101955) Bennu; Asteroid surface; Equilibrium points; OSIRIS-REX